Análisis del manejo presupuesto y su incidencia en la gestión de inventarios de medicamentos del distrito de salud 12D06 Buena Fe - Valencia periodo 2017-2018 - Bustamante Toscano, Paola Vitalina (2019)
The Ministry of Public Health of Ecuador in june 2014 creates Planning Zone No. 05 where it districts by provinces and cantons various Health Districts, that is where it opens in october 2014 Health District 12D06 Buena Fe- Valencia, located in the canton of Valencia, Los Ríos Province, which has been serving the community with priority and immediate attention in gynecology, obstetrics, dentistry, psychology and general medicine services. To determine the efficiency and effectiveness in the acquisition, storage and distribution of inventories, it is necessary to review the administrative management of this entity, in order to improve the distribution of medical equipment, medicines and medical supplies of each health center. The objective of the present investigation is oriented to analyze the budgetary management and its incidence in the management of inventories of medicines of the Health District 12D06 Buena FeValencia, being the problem of investigation How the budgetary management affects in the management of the inventory of medicines of the Health District 12D06 Buena FeValencia? The same is based on a descriptive research, oriented to analyze, describe and if necessary to modify the present reality of the nature of the study problem. The results obtained reflect an adequate budget execution, the indicators of management of the supply of medicines are favorable, and the administrative management covers 76% of medical attention, since 24% of the population goes to other health services. The research aims to generate guidelines for the proper use of the budget and inventory management. Key words: budget, administration, inventory, management, health.